Evaluating immunological and inflammatory changes of treatment-experienced people living with HIV switching from first-line triple cART regimens to DTG/3TC vs. B/F/TAF: the DEBATE trial - Cossarizza, Andrea; Cozzi-Lepri, Alessandro; Mattioli, Marco; Paolini, Annamaria; Neroni, Anita; De Biasi, Sara; Tartaro, Domenico Lo; Borella, Rebecca; Fidanza, Lucia; Gibellini, Lara; Beghetto, Barbara; Roncaglia, Enrica; et al. (Frontiers in Immunology, 2023)
Background The aim of this randomized clinical trial (RCT) was to compare immunological changes in virally suppressed people living with HIV (PLWH) switching from a three-drug regimen (3DR) to a two-drug regimen (2DR). Methods An open-label, prospective RCT enrolling PLWH receiving a 3DR who switched to bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) or dolutegravir/lamivudine (DTG/3TC) was performed. Blood was taken at baseline and months 6 and 12. The primary outcome was the change in CD4+ or CD8+ T-cell counts and CD4/CD8 ratio over time points. The secondary outcomes were the changes in immunological and inflammatory parameters. Parametric mixed-linear models with random intercepts and slopes were fitted separately for each marker after controlling for potential confounders. Results Between the two arms (33 PLWH each), there was no difference in CD4+ or CD8+ T cells, CD4/CD8 ratio, and IL-6 trajectories. PLWH switching to DTG/3TC had increased levels of both transitional memory and terminally differentiated CD4+ T cells (arm–time interaction p-value = 0.02) and to a lesser extent for the corresponding CD8+ T-cell subsets (p = 0.09). Significantly lower levels of non-classical monocytes were detected in the B/F/TAF arm at T6 (diff = −6.7 cells/mm3; 95% CI; −16, +2.6; p-value for interaction between arm and time = 0.03). All differences were attenuated at T12. Conclusion No evidence for a difference in absolute CD4+ and CD8+ T-cell counts, CD4/CD8 ratio, and IL-6 trajectories by study arm over 12 months was found. PLWH on DTG/3TC showed higher levels of terminally differentiated and exhausted CD4+ and CD8+ T lymphocytes and non-classical monocytes at T6. Further studies are warranted to better understand the clinical impact of our results. Clinical Trial Registration https://clinicaltrials.gov, identifier NCT04054089.